2020
DOI: 10.2147/trrm.s235488
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dietary Supplement Use in Live Kidney Donors and Recipients</p>

Abstract: Background: Dietary supplement use in living kidney donors (LKDs) and kidney transplant recipients (KTRs) provides care challenges due to drug interactions, limited data, and lack of management guidelines. The study purposes were to describe supplement use patterns and intra/postoperative complications in these populations. Methods: A single-center retrospective review of LKDs and KTRs from September 2016-2018 was conducted. Supplement information was collected at evaluation and preoperative visits. Supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…A prior study of LKDs from our center identified a pre-donation dietary supplement prevalence of 24%. 7 The current study identified dietary supplement use among half of LKDs; however, the classification of dietary supplements in our study included micronutrients (vitamins/minerals) which were excluded in our prior study. Unlike prescription and over-the-counter medications, dietary supplements are not regulated by the U.S. Food and Drug Administration and are not subject to the same scrutiny regarding their efficacy, safety, and purity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A prior study of LKDs from our center identified a pre-donation dietary supplement prevalence of 24%. 7 The current study identified dietary supplement use among half of LKDs; however, the classification of dietary supplements in our study included micronutrients (vitamins/minerals) which were excluded in our prior study. Unlike prescription and over-the-counter medications, dietary supplements are not regulated by the U.S. Food and Drug Administration and are not subject to the same scrutiny regarding their efficacy, safety, and purity.…”
Section: Discussionmentioning
confidence: 99%
“…21 Similar studies have found greater supplement identification with transplant pharmacist-conducted medication histories, underscoring the value of an interdisciplinary, team-based approach. 7,22 With frequent use of dietary supplements among LKD candidates, appropriate identification and counseling are imperative to maintain the health of these patients as well as preserve the renal function of the unilateral kidney.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations